Playing with Words: The Securitization Construction of “Refugee” in ASEAN Politics - Irawan Jati; Emily Sunderland (Universitas Muhammadiyah Yogyakarta, 2018)
ASEAN is playing with words among migrant, immigrants, asylum seekers, trafficked people and smuggled people terms to describe the enormous forced human movement from Myanmar. These terms are the representation of ASEAN’S securitization of humanitarian issues. It is unfortunate to see ASEAN unwillingness to entitle the term refugee where all of the necessary aspects are fulfilled. ASEAN has taken a very cautious political linguistic measure by evading the word “refugee” in their political dictionary. This article would like to examine the questions: why and how ASEAN securitized the refugee issue? And what are the political consequences for ASEAN if it keeps standing on its securitization policy? The discussion of this paper will be presented in Constructivist perspective approach. It argues that the construction of refugee in ASEAN is greatly influenced by its values that construct its collective security. In this respect, ASEAN is neglecting its role and identity as the defender of human rights in the region. Consequently, ASEAN’s refusal to comply with the international human rights regime will result in the organization in losing credibility and integrity.